Understanding Soil-Moisture Sensor Data - Schumann, Arnold; Waldo, Laura (EDIS, 2017)
In conclusion, citrus irrigation with soil water sensors is very effective and incorporates instant feedback information to the user which is not readily available from other irrigation scheduling tools using daily ET or historical ET records. Not all soil water sensors are equally effective, and the TDR model and brand shown in this case study was deliberately chosen for its proven accuracy and reliability. Proper installation of the sensors is also important, but beyond the scope of this article.